TRIM8 as a predictor for prognosis in childhood acute lymphoblastic leukemia based on a signature of neutrophil extracellular traps - Tin, Waihin; Xiao, Cuilan; Sun, Kexin; Zhao, Yijun; Xie, Mengyun; Zheng, Jiayin; Wang, Ying; Liu, Sixi; Yu, Uet (Frontiers in Oncology, 2024)
Background: Neutrophil extracellular traps (NETs) can be attributed to metastasis, occurrence and immune evasion of cancer cells. We investigated the prognostic value of NET-related genes in childhood acute lymphoblastic leukemia (cALL) patients.Methods: Differential gene expression analysis was conducted on samples collected from public databases. Grouping them based on expression level of NET-related genes, we assessed the correlation between immune cell types and risk score for having poor prognosis of cALL, with evaluation for sensitivity of drugs used in cALL. We further divided the groups integrating survival data. Subsequently, methods including multivariable Cox algorithms, least absolute shrinkage and selection operator (LASSO) and univariable were utilized to create a risk model predicting prognosis. Experiments in cell line and animals were performed to explore the functions of TRIM8, a gene selected by the model. Using lentivirus to validate TRIM8 in mice with T-ALL and B-ALL.Results: Kaplan-Meier (KM) analysis underscored the importance of differentially expressed genes identified in the groups divided by genes participated in NETs, with enrichment analysis showing the mechanism. Correlation analysis revealed significant associations with B cells, NK cells, mast cells, T cells, plasma cells, dendritic cells and monocytes. The IC50 values of drugs such as all-trans-retinoic acid (ATRA), axitinib, doxorubicin, methotrexate, sorafenib and vinblastine were increased, while dasatinib exhibited a lower IC50. A total of 13 NET-related genes was selected in constructing the risk model. In the training, testing and merged cohorts, KM analysis demonstrated significantly improved survival for low-risk cALL patients compared to high-risk cALL patients (p < 0.001). The area under the curve (AUC) indicated strong predictive performance. Experiments in Jurkat and SUP-B15 revealed that TRIM8 knockdown decreased the proliferation of leukemia cell lines. Further experiments demonstrated a more favorable prognosis in mice with TRIM8 knockdown leukemia cells. Results of cell lines and animals showed better outcomes in prognosis when TRIM8 was knocked down.We identified a novelty in prognostic model that could aid in the development of personalized treatments for cALL patients. Furthermore, it revealed that the expression of TRIM8 is a contributing factor to proliferation of leukemia cells and worsens prognosis of cALL.